Gender, language and culture : a study of Japanese television interview discourse - Tanaka, Lidia (Studies in language companion series, 2004)
This book analyzes the relationship between gender, age and role in Japanese television interviews. It covers a wide range of topics on Japanese communication; cultural and gender variables are interwoven in the interpretation of the findings. The study shows how participants interact through language and how they project their identities in the context of the interview. Based on a qualitative analysis, speech in mixed and same gender interactions is analysed, turntaking, terms of address and aizuchi (listener's responses) are examined. The findings reveal interesting characteristics of all-fe.